Risk factors for urinary bladder cancer: a hospital-based case-control study - Chaisurin, Patcharin; Sittisombut, Sudarat (Biomedical Sciences and Clinical Medicine, 2024)
The aim of this study was to determine risk factors for urinary bladder cancer at a university hospital in northern Thailand. A case-control study included 85 patients with newly diagnosed urinary bladder cancer, 170 patients without an oncological disease, and controls matched according to gender and age (± 5 years). The results showed that several factors associated significantly with urinary bladder cancer such as prolonged cigarette smoking, continual alcohol consumption and rainwater intake. In addition, some types of employment such as farming, laboring and government service also were related signifi cantly to urinary bladder cancer. Further efforts should be made to find effective strategies for reducing or stopping cigarette smoking and alcohol consumption. Meanwhile, exploration of why rainwater intake, laboring and farming are related to urinary bladder cancer should be performed immediately.